How reading strategies do influence reading comprehension by english students of readings and conversation l as a Foreign Language (EFL) at the University of El Salvador, Foreign Language Department, semester ll, 2015. - Castellón Cruz, Karla María
Reading is considered as one of the most important and useful components for students. Reading strategies enable learners to comprehend any type of texts, which after some time will make them have greater understanding. As such, mastering reading strategies is considered essential for learners. In order to create successful language learning environment in a reading classroom, educators need to help learners to identify their reading needs. In the long term, this will help educators to plan and meet the needs to the EFL learners’ requirements when they read. Reading strategies are no doubt an important criterion in students’ lives. However, very often, learners face obstacles when they come across reading materials. For instance, the assistance of reading strategies will aid language learners in becoming good readers. These strategies will further assist them in their academic reading as well. This study investigates how reading strategies influence reading comprehension by English students as Foreign Language (EFL). To gather the information required for this study, the instruments required will be a checklist, an interview and a test. The checklist will be used to take notes and see the students’ attitude, behavior and how reading strategies are used by them. Also, there will be a group of students taken from the class to be interviewed with semi-structured questions addressing their knowledge about reading strategies, their thought and opinion about the teacher’s methodology towards the reading strategies, the way students developed reading skill to construct comprehension, etc. finally, there will be a test to measure the use of readings strategies. Students will take this test twice, one time at the beginning of the course even if students do not anything about reading strategies and another time after they have seen readings strategies this time student will take the test being aware of readings strategies. So, in a way there will be a kind of comparison to see if students were influenced by readings strategies. The participants will be students enrolled in one group of Readings and Conversation I. The results of the test will be analyzed through statistical analysis. With the results that the researchers will get it is expected that these reading strategies could be more used as a teaching aid by educators to make reading both fun and educational. Nonetheless, with these strategies educators can facilitate learners to become exceptional readers.